Teacher of Preachers: Sue McBeth and Her Mission to the Nez Perce - Hoyle, Lydia (Missiology, 1999)
Sue McBeth was one of many single Protestant women missionaries who served among the Native Americans in the nineteenth century. Like the majority, she worked as a teacher. Her teaching, however, was not confined to children. Working among the Nez Perce, McBeth trained a generation of ministers who led the tribal Presbyterian churches. Although physically weak, McBeth was tenacious of spirit. She knew what she was called to do and would not allow governmental or denominational entities to deter her. Through her life, one can see the empowering nature of the missionary calling.